Esporulação de C. graminicola (ces.) wils. Do sorgo (Sorghum bicolor) (L.) Moench - Minussi, Elocy; Kimati, Hiroshi (Revista do Centro de Ciências Rurais, 2008)
Utilizando-se 4 isolados de Colletotrichum graminicola (Ces.) Wils. provenientes de diferentes localidades estudou-se o efeito de: a) meios de cultura; b) Superposição de discos de papel filtro nos meios solidificados e c) Regime luminoso. Isolados desenvolvidos em meio de aveia com superposição de papel filtro e mantidos sob luz continua esporulam abundantemente. Abstract The influence of the following factors on sporulation was tested by using of C. graminicola of Sorghum from four different localities: a) artificial media; b) filter paper discs placed on top of the artificial media and c) light regime. The isolates in an oat medium with filter paper on top and maintained under continuous light sporulated abundantly.